2011
DOI: 10.1155/2011/867674
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of Antiretrovirals during Pregnancy

Abstract: Combination antiretroviral therapy (CART) dramatically decreases mother-to-child HIV-1 transmission (MTCT), but maternal adverse events are not infrequent. A review of 117 locally followed pregnancies revealed 7 grade ≥3 AEs possibly related to antiretrovirals, including 2 hematologic, 3 hepatic, and 2 obstetric cholestasis cases. A fetal demise was attributed to obstetric cholestasis, but no maternal deaths occurred. The drugs possibly associated with these AE were zidovudine, nelfinavir, lopinavir/ritonavir,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Pregnant women received a clinician-prescribed antenatal ARV regimen that consisted of cART (≥3 ARV from ≥2 ARV classes) in most cases; modifications during the pregnancy were based on viral genotype, virologic response, safety, and tolerability, as previously described [ 33 35 ]. PI serum levels were routinely monitored and doses adjusted to achieve a trough above the 25th percentile for nonpregnant adults.…”
Section: Methodsmentioning
confidence: 99%
“…Pregnant women received a clinician-prescribed antenatal ARV regimen that consisted of cART (≥3 ARV from ≥2 ARV classes) in most cases; modifications during the pregnancy were based on viral genotype, virologic response, safety, and tolerability, as previously described [ 33 35 ]. PI serum levels were routinely monitored and doses adjusted to achieve a trough above the 25th percentile for nonpregnant adults.…”
Section: Methodsmentioning
confidence: 99%
“…Further functional studies in brush border membrane preparations for substrates of these transporters, such as metformin (Terada et al, 2006) and antiretroviral drugs (Schuetz et al, 1999;Huisman et al, 2002), should be performed to determine the relevance of the observed protein changes. These chemicals are renally eliminated and have been under-investigation for prescribing during pregnancy (Unadkat et al, 2007;Weinberg et al, 2011;Silva et al, 2012). Likewise, circulating bile acids are increased during pregnancy, and their renal secretion may be reduced during pregnancy because of decreased Mrp4 expression (Rius et al, 2006).…”
Section: Tablementioning
confidence: 99%
“…Nevertheless, possible short-and long-term adverse effects of these medications in both the mother and the fetus should be considered [18,19]. The use of protease inhibitors during pregnancy has been associated with an increase in premature deliveries and low birth weight [20,21].…”
Section: Discussionmentioning
confidence: 99%